Green and Clean Mobility: A Study of Trans Batam's Management and Administration in Supporting Sustainable Transportation - Susanto, Oma; Tibrani, Tibrani; Ramadhan, Denny Ammari (Dinasti Research, 2026)
This study aims to comprehensively analyze how Trans Batam's infrastructure management contributes to the principles of Green & Clean Mobility, a public transportation concept focused on efficiency, quality and public access. The research focuses on three main management aspects: (1) facility suitability; (2) governance mechanisms and operational management; and (3) sustainability principles.The analysis was conducted using an exploratory quantitative approach, assessing each research dimension with SmartPLS 4.3.0.1. One hundred respondents participated during the research period and expressed their willingness to volunteer to support the research. The results indicate a significant correlation between each exogenous and endogenous dimension. They are integral to driving the quality of Trans Batam's transportation services. Furthermore, this is supported by an R2 value of 67.2% (0.672). This demonstrates that the involvement of the research dimensions does contribute to improving Trans Batam's public transportation services. Furthermore, the Q2 value of 0.485 indicates strong predictive relevance, indicating that the model not only explains variation within the sample but also has adequate predictive capacity. Ultimately, this research can serve as policy recommendations and contribute to the development of an inclusive, efficient and sustainable public transportation service model—Trans Batam